Daya Saing Usahatani Jagung Hibrida di Kabupaten Muna Barat - Ade Sahrul; Sitti Aida Adha Taridala; Ilma Sarimustaqiyma Rianse (Universitas Halu Oleo, 2022)
The purpose of this study was to analyze the competitiveness of hybrid maize farming in Muna Barat Regency. Data collection was carried out in May - July 2021. The population in this study were all 415 hybrid corn farmers in Muna Barat Regency. Determination of the sample is done by using the cluster random sampling method, where the population is grouped by region, then the sample is selected randomly. Determination of the number of samples using the Slovin formula so that the number of samples obtained is 64 people. The data collected includes: the use of tradable inputs (fertilizers, pesticides, fuels, production machinery) and non-tradable inputs (land area, seeds, labor and production equipment) and outputs (production and selling prices). The data collection technique used is an interview using a questionnaire or a question guide. Analysis of the data used is the Policy Analysis Matrix (PAM). The results of the study show that hybrid corn farming in West Muna Regency has a competitive advantage, both based on indicators of competitive advantage with a PCR value of 0.29; or based on indicators of comparative advantage with a DRCR value of 0.07.Keywords: competitiveness; hybrid corn; Policy Analysis Matrix (PAM)